PENGEMBANGAN MEDIA WORDWALL BERBASIS KEARIFAN LOKAL PADA PEMBELAJARAN MATEMATIKA SISWA KELAS V SD NEGERI 18 LUBUKLINGGAU - Saputra, Ardian; Supriyanto; Elya Rosalina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT This study aimed to develop a local wisdom-based Wordwall learning media for mathematics instruction for fifth-grade students at SD Negeri 18 Lubuklinggau that meets the criteria of validity, practicality, and effectiveness. The study employed the Research and Development (R&D) method using the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects included material experts, media experts, language experts, a fifth-grade teacher, and fifth-grade students at SD Negeri 18 Lubuklinggau. Data were collected through interviews, validation questionnaires, teacher and student response questionnaires, and learning achievement tests. The data were analyzed using descriptive qualitative and quantitative techniques. The results indicated that the local wisdom-based Wordwall learning media achieved an average validity score of 90.67%, which falls into the very valid category. The practicality test yielded an average score of 92.14%, indicating that the media is very practical. Furthermore, the effectiveness test, based on the N-Gain analysis, produced a score of 0.67, which is categorized as moderate, indicating that the media is sufficiently effective in improving students' mathematics learning outcomes. Therefore, the local wisdom-based Wordwall learning media is considered suitable for use in fifth-grade mathematics learning as it fulfills the criteria of validity, practicality, and effectiveness.